Ethics of Evolution, Evolution of Ethics. Can Small Differences in View on Human Evolution Can Hide a Divide in Metaethical and Metaphysical Positions? - Tabisz, Dominik (Folia Philosophica, 2018)
“Evolution and Ethics” is both a fundamental problem to consider for any philosopher who accepts Darwin’s theory and title of two papers. First written by Thomas H. Huxley second by John Dewey. The former was philosophizing naturalist, creator of the early curriculum for biology. Despite supporting theory of evolution he opposed deriving any ethical principles from evolution. The latter was a philosopher associated with pragmatism and theories of pedagogy. He was also a supporter of evolutionism. In his paper “Evolution and Ethics” he commented “Romanes lecture” delivered by Huxley. Pragmatist proposed different understanding of the process of evolution and (what this paper try to show) different Ethical position induced from an understanding of the mentioned process. Huxley’s skeptical view on evolutionary ethics can be founded not only on his understanding of this process. His skepticism can be interpreted as opposition to any form of naturalism in ethics.